Adoption and understanding of green technology innovation among procurement proton’s staff: A case study of an automotive industry / Nurshazwani Muhamad Mahfuz - Muhamad Mahfuz, Nurshazwani (Bachelor of Science (Hons) Statistics, 2015)
This research aim to examine how adoption and understanding of green technology innovation is impacted by procurement PROTON’S staff. The study focus on Malaysia automobile manufacturer which is Perusahaan Otomobil Nasional Sdn Bhd where currently embarks smart green technology in its production of car. The objective of the study is to identify the factor that effect the innovativeness of green technology including training, team development, organizational culture and knowledge sharing. All Procurement staffs were selected as a respondent. The department is known as “Department Technical Procurement”. This study involved 144 of respondents by using stratified random sampling. Structural Equation Modelling (SEM) approach is used to investigate the relationship among variables. SEM also is a confirmatory method providing a comprehensive means for assessing and modifying the measurement models as well as structural model. The result of independent samples t-test shows there is significant difference of the gender and having hybrid car. Analysis of Variance (ANOVA) shows there is a significant difference of the age, and working experience on innovativeness of green technology. Furthermore, there is significant difference between training and organizational culture. Besides, knowledge sharing is significant on innovativeness of green technology